The opening movements of the Phenomenology of spirit : transcendental argument or phenomenological exposition? - Hewitt, Keith, 1959- (2000)
Thesis (M.A.)--Memorial University of Newfoundland, 2000. Philosophy Bibliography: leaves 123-124 Charles Taylor in his essay "The Opening Arguments of The Phenomenology" argues that the first three chapters of Hegel's Phenomenology of Spirit are an essay in transcendental argument. This suggests that Hegelian phenomenology is principally concerned with establishing what the transcendental preconditions of human knowledge and action are. In this thesis I will argue that Hegel's work should be seen as an attempt to move beyond an idealism that simply appeals to subjective reason, and thus the opening chapters of the "Phenomenology" should not be construed as a transcendental argument. -- Hegel is often critical of transcendental method, and of modem epistemology generally, precisely because it views knowledge as primarily a dimension of human self- consciousness. It is Hegel's view that Kantian epistemology, for example, is flawed in that it is a procedure that assumes an original distinction between our consciousness and the world, which once assumed can never be bridged. And while Hegel recognizes that knowledge in some manner involves self-conscious reason, he calls for a reversal of the modem predilection to ground it solely within such a reason. -- Accordingly, in Chapter One I examine Hegel's concept of phenomenology and his criticism of subjective idealism; in Chapter Two, in the light of this criticism, I address Taylor's view of transcendental argument, and his claim that phenomenological argument is similar in structure; and finally, in Chapter Three, the specific issue of whether the opening movement of the Phenomenology of Spirit is transcendental in form is dealt with.